1995
DOI: 10.1007/3-540-60246-1_158
|View full text |Cite
|
Sign up to set email alerts
|

From timed automata to logic — and back

Abstract: One of the most successful techniques for automatic verification is that of model checking. For finite automata there exist since long extremely efficient model-checking algorithms, and in the last few years these algorithms have been made applicable to the verification of real-time automata using the region-techniques of Alur and Dill. In this paper, we continue this transfer of existing techniques from the setting of finite (untimed) automata to that of timed automata. In particular, a timed logic L ν is put… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 23 publications
0
38
0
Order By: Relevance
“…In particular, by using the standard region technique, it has been shown that region reachability for timed automata is decidable [3]. This fundamental result and the technique help researchers, both theoretically and practically, in formulating various timed temporal logics [2,4,5,6,22,25,26,27] and developing verification tools [21,28,24].…”
Section: Introductionmentioning
confidence: 90%
“…In particular, by using the standard region technique, it has been shown that region reachability for timed automata is decidable [3]. This fundamental result and the technique help researchers, both theoretically and practically, in formulating various timed temporal logics [2,4,5,6,22,25,26,27] and developing verification tools [21,28,24].…”
Section: Introductionmentioning
confidence: 90%
“…A characteristic formula is a significantly complex formula describing the entire behaviour of the timed automaton. Here we describe how we can in general generate a simpler formula using a fragment of the logic described in [14]. The logic we use for generating the distinguishing formula has been described in [1] which is a timed extension of Hennessy-Milner logic and does not contain any recursion as opposed to the logic used in [14].…”
Section: Deciding Timed Bisimulationmentioning
confidence: 99%
“…Here we describe how we can in general generate a simpler formula using a fragment of the logic described in [14]. The logic we use for generating the distinguishing formula has been described in [1] which is a timed extension of Hennessy-Milner logic and does not contain any recursion as opposed to the logic used in [14]. The set M t of Hennessy-Milner logic formulae with time over a set of actions Act, set D of formula clocks (distinct from the clocks of any timed automaton) is generated by the abstract syntax…”
Section: Deciding Timed Bisimulationmentioning
confidence: 99%
See 2 more Smart Citations